(untitled) (Hematology Meeting Reports, 2009)
The ontogeny of immune system starts early in the embryo continues during fetal life and is completed only several years after birth.1 In addition, the fetus, who develops in a highly protective germ-free environment, lacks antigenic experience. These factors cause problems of immunological adaptation during the transitional period from the intra- to the extra-uterine life, and are responsible for the physiological immaturity of the immune function in newborn infants.2